Acute otitis media in the first two months of life: characteristics and diagnostic difficulties. Issue 8 (12th March 2008) - Berkun, Y; Nir-Paz, R; Ami, A Ben; Klar, A; Deutsch, E; Hurvitz, H
Abstract : Objective: To assess the clinical and laboratory features of acute otitis media (AOM) in infants younger than 2 months, to look for factors predicting bacterial otitis, and to evaluate the accuracy of AOM diagnosis among paediatricians. Methods: The study population comprised a cohort of 277 hospitalised infants up to 61 days old that were treated for the first episode of AOM in a paediatric department. We reviewed their medical records and analysed the demographic, clinical and laboratory data, and the diagnosis made by both paediatricians and otolaryngologists. Results: Presenting symptoms were mainly respiratory (70.0%) and fever (62.5%). The most common pathogens were Streptococcus pneumoniae and Haemophilus influenzae . Gram-negative bacilli grew in 10.5% of the infants. Multivariate analysis revealed that AOM in the second month of life was associated with male gender, concurrent bronchiolitis and diarrhea. Although high leukocyte count was associated with bacterial pathogen, more than 70% of the patients with positive culture had normal white blood cell counts. The paediatrician diagnosed only 45% of the patients subsequently diagnosed with AOM by an otolaryngologist. Conclusions: The absence of predictors for bacterial infection in more than 70% of bacterial AOM suggests that empirical antibiotic treatment should be advised for the young infants with AOM even when afebrile and with normal laboratory profile. A low diagnostic rate of AOM by the paediatrician emphasizes the need for improvement in examination skills and instrumentation to allow a thorough ear evaluation in children of a very young age.